Advances and Technical Standards in Neurosurgery : Volume 42 - Schramm, Johannes (Advances and Technical Standards in Neurosurgery,, 2015)
This volume of Advances and Technical Standards in Neurosurgery covers some important new developments in functional neurosurgery and endovascular therapy. In the Technical Standards section a variety of topics are considered, including optic pathway gliomas, pineal lesions, cavernous sinus meningiomas, and the eternal problem of minor and repetitive head injury. Endovascular treatment of a variety of lesions is now common practice, and the state of the art in endovascular treatment for acute ischemic stroke is reviewed. An appraisal of the evidence on whether there is a place for microsurgical vascular decompression for essential hypertension raises interesting questions. The volume is completed by contributions on neurosurgical treatment of cluster headaches and occipital nerve stimulation.